Regional Educational Reform in Thailand: Needs Assessment and Personnel Management 4.0 for the 21st Century - Moonsarn, Boonchuay; Phoncharoen, Chotniphitphon; Jedaman, Pornchai; Kenaphoom, Sanya (International Journal of Sociologies and Anthropologies Science Reviews, 2022)
Personnel management 4.0 was employed as the framework for exploring the educational personnel’s perspectives on the regional educational reform in Thailand. This study aims to use the needs assessment and personnel management 4.0 for the 21st-century framework to understand the regional educational reform in Thailand. The mixed-method research methodology was employed in this study. Quantitative was collected by needs assessment through a questionnaire survey with the educational personnel from four regions in Thailand. Qualitative was collected by participatory action learning through brainstorming to the data. Needs assessment showed that the internal and external environment was at a high level and the desired condition was at a very high level. High needs regarding organizational plan leadership and strategic planning, measurement and knowledge management and focusing on organization, respective. Also, the relationship among educational administrators’ perspectives on regional educational reform under the personnel management 4.0 framework was statistical significance. Key findings are discussed and their implications are also presented.